5/3x+1/3x=8/3+8/3x

Simple and best practice solution for 5/3x+1/3x=8/3+8/3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/3x+1/3x=8/3+8/3x equation:


x in (-oo:+oo)

(5/3)*x+(1/3)*x = (8/3)*x+8/3 // - (8/3)*x+8/3

(5/3)*x+(1/3)*x-((8/3)*x)-(8/3) = 0

(5/3)*x+(1/3)*x+(-8/3)*x-8/3 = 0

-2/3*x-8/3 = 0 // + 8/3

-2/3*x = 8/3 // : -2/3

x = 8/3/(-2/3)

x = -4

x = -4

See similar equations:

| -8(t-7)-7(2t+1)=-17 | | 7(x-4)=6(x+1)-3 | | 5(40-(40-x))+10(40-x)+25x=405 | | -59=-5(4a-4)+1 | | -x-(13+4x)=-3(5-9k)+2 | | -0.8(2x-6)=1.7(3-x) | | 3y+(-11y)= | | 12x^2-81x-3/7=0 | | x/3-9=11 | | 12x^2-81x-3/7 | | -15t-9+8t=4t-3 | | 4+-1x=-1x+4 | | 0.5x-0.1=0.4-0.6(9-2x) | | 3y-7=2y+5 | | 3-6x=-80-5x | | 4+-1x=1x+4 | | x^2+1x=272 | | -2y+8=3y+28 | | 6x^24= | | 3x+1.5x+x+180=455 | | 6(4x-3)-10= | | 7x+9x-69=46-7x | | 2(9x-1)=99-7(3-4k) | | 8n-3.5=-20 | | z/2+1=7z/2 | | 10(1+30b)=-20 | | 2x+8-k=-3 | | 24-4= | | 20z+80=140+10x | | -(3x-2)-(x+4)=-(2x-2)-(2x+4) | | 10+30b=-2 | | 11520=32x^2+64x |

Equations solver categories